Cooperative Integrated Reading and Composition Technique for Improving Content and Organization in Writing - Faisal Mustafa; Nanda Marlina Abdul Samad (Universitas Syiah Kuala, 2015)
This study examines the Cooperative Integrated Reading and Composition (CIRC) technique for improving students’ English writing skills, specifically in content and organization when focused on writing recount texts. This experimental research used random sampling and random assignment to determine the control group (CG) and the experimental group (EG). Pre- tests, treatment or teaching and post-tests were done to both groups. The study was conducted with 60 second year students from a junior high school in Banda Aceh, Indonesia. Students’ mean scores for the pre-test in the CG were 40.76 and 60.76 for the post-test, meanwhile students’ mean scores for the pre-test in the EG were 40 and 72.69 for the post-test. Thus, the t-test between both groups was 9.39 and the t-table was 2.056 which used 0.05 as the level of significance for this research. Because the t-test value was higher than the t-table (9.39 2.056), Ha was accepted and Ho was rejected. Therefore, the CIRC technique can improve the content and organization of students’ writing in doing recount texts. In addition, because students work in groups, they have more opportunity to learn and share their ideas with other students to produce better writing.